Analisis Dampak Fenomena Peningkatan Urban Heat Island Kota Semarang Tahun 2024 - Radite Ranggi Ananta; Casriyah Casriyah; Moh. Rayya Ilham Rehardiyan; Lovi Nugiantika Pasha (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Climate change has become a global issue with significant impacts, especially in urban areas, with the Urban Heat Island (UHI) phenomenon being one of its catalysts. This research aims to analyze the effect of the Urban Heat Island phenomenon in Semarang City in 2024, triggered by population growth, urbanization, and land use changes. This research uses spatial analysis methods based on Google Earth Engine (GEE) and Landsat-8 satellite imagery to calculate surface temperature. The sampling technique uses the Purposive Sampling method. The population of this study consists of people residing or staying in the city of Semarang, and the samples are the Garnisun Field area representing South Semarang, the Tugu Muda area representing Central Semarang, and the Old Town area representing North Semarang. The research results show that the highest temperature was recorded in the Tugu Muda area, which was 37.3°C, followed by the Garnisun Field at 36.8°C and the Old Town at 36.4°C. The main factors contributing to the intensity of UHI include the conversion of vegetated land into built-up areas, emissions from motor vehicles, and the lack of green open spaces. The recommended mitigation measures are implementing environmentally friendly technologies such as green roofs, green walls, and high-albedo materials, as well as expanding green spaces in residential and commercial areas.